Effect of School Water, Sanitation, and Hygiene on Health Status Among Basic Level Students' in Nepal - Mohan Kumar Sharma; Ramesh Adhikari (SAGE Publishing, 2022)
Background: Access to drinking Water, Sanitation, and Hygiene (WASH) at schools are the basic determinants of a child's right to healthy and quality education. In Nepal, most of the schools had limited WASH facilities, including separate sanitation facilities for girls. The limited WASH facilities, unsafe drinking water, poor sanitation, and hygiene practices result in irresponsible behaviors that directly impede on students' health. This study examines the association between WASH services and health status of basic level students', ranging sixth to eighth grades. In Nepal, basic level education consists up to eighth standards from grade 1. Methods: The study applies causal-comparative research design within 2 groups; 1 having improved WASH and another without improved WASH services at the schools in Dhanusha and Chitwan districts of Nepal. Each group consists 2 schools, so altogether 4 schools were included in this study. Total 768, equal 384 respondents were selected from each improved and without improved WASH facilities. The study was conducted in between January and March 2021 at a single-phase time. The sample size was calculated using the standard statistical formula for the infinite population. The study applied quantitative research method, including 3 sorts of analysis; univariate, bivariate, and the multivariate. The univariate was applied to analyze the frequency and percentages of the respondents. Bivariate analysis was made applying chi 2 test in order to show the association between 2 variables, whereas the multivariate logistic regression was performed through multilevel modeling to show the effects of school WASH facilities on students' health status. Results: Out of 768 students', 384 (50%) were from improved and 384 (50%) were from unimproved WASH facilities at schools. More than two third (64%) of respondents from the unimproved and higher than two fifth (41%) from the improved schools got sickness ( P  <.001). Further, three fifth (59%) of respondents aged 15 to 19 and higher than half (51%) of respondents ages of 10 to 14 years got sickness ( P  <.05). Most (57%) of the female respondents had sickness compared to males (47%), ( P  <.05). More than two-thirds (67%) of respondents from Dalit and nearly two-thirds (62%) of respondents from Brahmin/Chhetri-Terai more often found being sick in unimproved schools compared to other castes (55%), Janajati (43%), and Brahmin/Chhetri-Hill (39%) ( P  <.001). The school WASH services has significant effect (cOR = 0.388, CI; 290-0.519, P  <.001) on students health status, even adjusting other socio-covariates (aOR = .442, CI; 0.302-0.646, P  <.001). The female respondents were more likely to fall sick (aOR = 678, CI; 0.502-0.915, P  <.01) compared to the male respondents keeping all other variables constant in the model. Conclusion: The study recommends to extend WASH awareness program to school families, particularly to the students as there is an evident need to increase preventive as well as the therapeutic efficacy of the potential infections.